Manfaat organisasi sekolah dan motivasi guru terhadap prestasi kerja guru SMP Negeri 04 Bangsalsari - Nurhafit Kurniawan (Universitas PGRI Madiun, 2017)
The design of this research was descriptive quantitative research that was a research about the data which was collected and expressed in terms of numbers. This research analyzed the data using numbers as a testing ground on the contribution of the relation between school organization, teacher motivation and the performance of elementary school teachers SMP Negeri 04 Bangsalsari. This research also used supporting qualitative data such as words or phrases that were arranged in the questionnaire, the results of consultation or interviews between researcher and informant. The research subjects in this research were SMP Negeri 04 Bangsalsari teachers. The objects of this research were the relations between three variables namely, School Organization (X1), Teacher Motivation (X2), and the Teachers' Performance (Y). Dependent variable in this research was the Teacher Performance while independent variables were the Motivation of Teachers and School Organization. The variables were then defined operationally in order to provide clues to how the variable measured. Based on the calculation of correlation analysis, both individually and collectively were significant. Then it was interpreted so it provided objective information and determined the contribution between variables.